2017
DOI: 10.1080/1331677x.2017.1355258
|View full text |Cite
|
Sign up to set email alerts
|

Why did some firms perform better in the global financial crisis?

Abstract: We explore what firm and macroeconomic factors assisted Chinese firms to resist the global financial crisis. We find that firms with higher top ten shareholder ratios or firms that are older exhibited saliently higher performance during the crisis, but performed poorly during the non-crisis period. Firm size has a notably negative impact on firm performance. Firms audited by the Big Four accounting firms have a significantly negative correlation with performance. During the crisis, stock markets became less ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 128 publications
(155 reference statements)
1
28
0
3
Order By: Relevance
“…due to the increased scrutiny of accounting practices. Facts such as weak investors' rights protection can provide insiders with incentives to extract private benefits by disguising the actual performance of the company (Fel ıcio et al, 2018;La Porta et al, 2000) and by obfuscating firm performance (Dick et al, 2017;Lee, Chen, & Ning, 2017;Leuz et al, 2003). The S.O.X.…”
Section: Institutional System and Real Activities Manipulationmentioning
confidence: 99%
“…due to the increased scrutiny of accounting practices. Facts such as weak investors' rights protection can provide insiders with incentives to extract private benefits by disguising the actual performance of the company (Fel ıcio et al, 2018;La Porta et al, 2000) and by obfuscating firm performance (Dick et al, 2017;Lee, Chen, & Ning, 2017;Leuz et al, 2003). The S.O.X.…”
Section: Institutional System and Real Activities Manipulationmentioning
confidence: 99%
“…Moreover, recent studies confirm that performance assessment is sensitive to the definition of family firms (Lee et al 2017 ). In terms of the financial condition of family firms, their performance in times of uncertainty, economic downturn, crisis, or recession seems essential.…”
Section: Literature Reviewmentioning
confidence: 88%
“…In case of inbound deals in India, Reddy (2015) found that number and value of cross-border acquisitions have markedly declined both in continents and in industries around the crisis. Researchers across the globe investigated the impact of subprime crisis on the financial performance of the companies; Madaleno and Barbuta-Misu (2019) for non-financial firms from European countries, Yap, Mohamed, and Chong (2014) for Malaysian manufacturing companies, Lee, Chen, and Ning (2017) for Chinese companies, Kontogeorgos, Pendaraki, and Chatzitheodoridis (2017) for Greek Cheese companies, Zhao, Jiang and Li (2015) in Asia, Mahajan and Singh (2013) for Indian corporate sector and found mixed results. This article examined the effect of subprime crisis while empirically investigating the impact of M&As or corporate performance.…”
Section: Theoretical Constructmentioning
confidence: 99%